Effect of chelating and antioxidant agents on morphology and DNA methylation in freeze‐drying rabbit (Oryctolagus cuniculus) spermatozoa. Issue 1 (8th November 2019) - Mercati, Francesca; Domingo, Paula; Pasquariello, Rolando; Dall'Aglio, Cecilia; Di Michele, Alessandro; Forti, Katia; Cocci, Paolo; Boiti, Cristiano; Gil, Lidia; Zerani, Massimo; Maranesi, Margherita
Abstract: Freeze‐drying (FD) has been exhaustively tried in several mammalian species as an alternative technique to sperm cryopreservation, but few studies have been done in rabbits ( Oryctolagus cuniculus ). The main objective of this study was to compare the protective effect of various antioxidants added to EDTA medium on structural and functional components of FD rabbit spermatozoa and on their status of global DNA methylation. FD media used were composed of basic FD medium (10 mM Tris‐HCl buffer and 50 mM NaCl) supplemented with either 50 mM EDTA alone (EDTA) or added with 105 µM of rosmarinic acid (RA, EDTA‐RA) or 10 µM of melatonin (MLT, EDTA‐MLT). The effect of each medium on the preservation of FD spermatozoon structure was evaluated with light and scanning electron microscopy ( SEM ). Global DNA methylation was quantified in all FD sperm samples as well as in fresh spermatozoa. Morphologically, fracture points were evidenced in the neck, mid and principal piece of the spermatozoon tail. No differences in spermatozoon fracture points were evidenced among FD treatments: intact spermatozoa were the largest ( p <  .01) category, whereas the most frequent ( p <  .01) injury was the neck fracture, resulting in tailless heads. At SEM, the head of spermatozoa showed a well‐conserved shape and intact membrane in all treatments. DNA methylation status was the same in all FD treatments. In conclusion, supplementation of EDTA, EDTA‐RA and EDTA‐MLT during FD preserved rabbit sperm morphological integrity and methylation status as well. Therefore, the difficulty of getting viable offspring using FD semen is likely unrelated to the impact of the lyophilization process on DNA methylation and morphology of lyophilized spermatozoa.